Modeling the 2023 Türkiye Earthquakes and Strain Accumulation Along the East Anatolian Fault Zone: Insights from InSAR, GNSS, and Small-Magnitude Seismicity, with Implications for the Seismic Potential at Rupture Terminations - Daniele Cheloni; Nicola Angelo Famiglietti; Aybige Akinci; Riccardo Caputo; Annamaria Vicari (Remote Sensing)
The 6 February 2023 MW 7.8 and MW 7.6 earthquakes in southeastern Türkiye ruptured more than 400 km of the East Anatolian Fault Zone (EAFZ), producing one of the most destructive seismic sequences in recent history. Here, we integrate InSAR data, a new GNSS velocity field, and small-magnitude earthquakes to investigate the coseismic deformation, rupture geometry, and interseismic strain accumulation along the EAFZ. Using elastic dislocation modeling with a variable-strike, multi-segment fault geometry, we constrain the slip distribution of the mainshocks, showing improved fits to the surface displacement compared to the planar fault model. The MW 7.8 event ruptured a number of fault segments over ~300 km, while the MW 7.6 event activated a more localized fault system with a peak slip exceeding 15 m. We also model two moderate events (MW 5.6 in 2020 and MW 5.3 in 2022) along the southwestern part of the Pütürge segment—an area not ruptured during the 2020 or 2023 sequences. GNSS-derived strain-rate and locking depth estimates reveal strong interseismic coupling and significant strain accumulation in this region, suggesting the potential for a future large earthquake (MW 6.6–7.1). Similarly, the Hatay region, at the southwestern termination of the 2023 rupture, shows a persistent strain accumulation and complex fault interactions involving the Dead Sea Fault and the Cyprus Arc. Our results demonstrate the importance of combining remote sensing and geodetic data to constrain fault kinematics, evaluate rupture segmentation, and assess the seismic hazard in tectonically active regions. Targeted monitoring at rupture terminations—such as the Pütürge and Hatay sectors—may be crucial for anticipating future large-magnitude earthquakes.